Collaboration of Shopee Indonesia and Tanjungpinang City PUSPA Forum in Digital Marketing Training for MSMEs in Tanjungpinang City: Kolaborasi Shopee Indonesia dan Forum PUSPA Kota Tanjungpinang dalam Pelatihan Digital Marketing UMKM di Kota Tanjungpinang - Siti Utari, Diah; Desmayeti Arfa; Andi Wika Waryanti; Nadya Aisyah Gustirani (Yayasan Ahmar Cendekia Indonesia, 2024)
Online product promotion training was carried out on February 26, 2024. Shopee Indonesia and the Tanjungpinang City PUSPA Forum collaborated to organize this activity. This basic class training is called